The relationship between nomophobia and psychiatric symptoms in adolescents - ARMAN, AYŞE; GÖKSU, MUHSİNE (TAYLOR & FRANCIS LTD, 2021)
Objective This study aimed to find out whether nomophobia levels are higher in adolescents with internalising or externalising disorders than healthy adolescents and to investigate the correlation of nomophobia levels with externalising and internalising symptoms. Methods K-SADS (Kiddie Schedule for Affective Disorders and Schizophrenia) was applied to 139 adolescents (ages 13-18) and they were asked to fill No Mobile Phone Questionnaire (NMP-Q) and Revised Child Anxiety and Depression Scale (RCADS), while the parents were asked to complete Conners Parent Rating Scale-48 (CPRS-48). Results There were no significant differences in nomophobia total scores between the three study groups. However, losing connectedness (LC) and not being able to access information (NAI) subscores were significantly higher in group with internalising disorder than healthy controls and there was no significant difference between group with externalising disorder and healthy group. Separation anxiety, social phobia, total anxiety, depression, hyperactivity and oppositional problems positively correlated with nomophobia total score. Conduct problems correlated with only LC. Total anxiety and hyperactivity predicted nomophobia total score. Conclusions Since anxiety and hyperactivity were predictors of nomophobia according to the study, adolescents with attention deficit hyperactivity disorder or anxiety disorder should be examined for nomophobia as well.
Keywords: Smartphone addiction; mobile phone overuse; anxiety; depression; hyperactivity; oppositional; MOBILE PHONE; PSYCHOMETRIC PROPERTIES; ADDICTION; STRESS